Geospatial modelling of soil geochemistry at national-scale for improved human nutrition - Chagumaira, Christopher (2022)
Mineral micronutrient deficiencies (MND), prevalent in Ethiopia and Malawi among most countries in sub-Saharan Africa, are linked to soil type. Dietary mineral intake is influenced by mineral content of edible portions of crops, and there is strong evidence that cereals grown in these regions have low uptake of micronutrients. The low nutrient uptake is attributed to soil conditions. Spatial information on soil and crop properties is therefore required to improve local estimates of MND risk in order to implement targeted and efficient interventions. Obtaining spatial information on soil micronutrients status and other relevant properties that affect their uptake requires substantial effort, and there are uncertainties in the resulting information, which depend, in part on the methods used for prediction and the sampling design. Therefore, it is necessary to use robust and efficient methods for spatial prediction which characterise the uncertainty of the predictions reliably. Furthermore, it is necessary that these uncertainties can be communicated effectively to stakeholder groups so that they can account for them at all stages from commissioning the survey through to making decisions based on the information.